Barriers and facilitators to uptake and promotion of influenza vaccination among health care workers in the community in Beijing, China: A qualitative study. Issue 14 (25th March 2022) - Yu, Mengke; Yao, Xi; Liu, Guangqi; Wu, Jiang; Lv, Min; Pang, Yuanjie; Xie, Zheng; Huang, Yangmu
Abstract: Background: In the prevention and control of influenza, it is important for healthcare workers (HCWs) to be vaccinated and recommend influenza vaccines to their patients. However, there is limited evidence on the factors influencing uptake and promotion of influenza vaccination to patients among HCWs in China. Methods: We conducted in-depth interviews among HCWs in community health centers, including general practitioners (GPs) and preventive health workers (PHWs), during January to February 2017. A total of 21 individuals, purposively selected from six community health centers covering central districts and remote suburbs in Beijing, were interviewed using semi-structured topic guides. Thematic analysis was used to analyze the interviews and coding framework was developed both inductively and deductively. Results: Identified factors influencing influenza vaccine uptake included knowledge, perception and recognition, and prior experience of vaccine uptake. All PHWs conservatively recommended influenza vaccine because of concerns about potential patient–doctor disputes. GPs rarely recommended vaccination under their own initiative because vaccine promotion was not their duties. Notably, we found that the division of work was an underlying reason for the different behaviors regarding vaccine uptake and promotion between GPs and PHWs. Conclusions: Our findings highlighted a combination of misconceptions and cognitive biases limiting influenza vaccine uptake among HCWs in China. Our findings indicate that promotion of health education regarding influenza vaccination should be implemented among HCWs. Importantly, the division of work greatly affects the behaviors of HCWs. GPs, who are at the front line in the doctor–patient relationship, have a critical role in influenza vaccination programs.